If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + 1) = -3 Reorder the terms: 12(1 + x) = -3 (1 * 12 + x * 12) = -3 (12 + 12x) = -3 Solving 12 + 12x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = -3 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = -3 + -12 12x = -3 + -12 Combine like terms: -3 + -12 = -15 12x = -15 Divide each side by '12'. x = -1.25 Simplifying x = -1.25
| 22=x-7.8 | | 14-5x=-52 | | 121=4x+7 | | 4(x-5)=2(x+2) | | x+15+75=x | | (x-lnx*2x)/x^4 | | -3x+8x=10 | | 2n-3/7=1n-2/5 | | x+15=x+75 | | -6x+8=-3x-10 | | 6x-3x=-15 | | x^2-2x=20.085 | | 3n-6n=-12 | | xsquared+6x+2=3 | | 5x+5-6x=1 | | -24=4(x+6) | | R-3-8=-12 | | y^2-16y-100=0 | | R-4-7r=-10 | | -3u-(-7)=-4 | | 4u+10=-5(u+7) | | 3x+x=2x-10 | | 3(9-3x)=27 | | 2(3a+9b)= | | 5.5(4.5b+6)=22.5+7b | | 8(y-3)=4y+4 | | 2x^3(x+1)=3x^2-(x-6) | | 2x-11=7x+6 | | 36=w+5w | | 5(8+7x)=390 | | -6x+4(x+8)=30 | | 5a-3whena=4 |